High Frequency Words in The Reading Section of TOEFL PBT Exercises - Aghnia Dianah Anwar; Tofan Dwi Hardjanto (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
English profeciency is one of the most important prerequisites to be fulfilled in applying for educational degrees, scholarships, or even jobs nowadays. Test of English as a Foreign Language (TOEFL) is one of the most common english profeciency tests to be taken in Indonesia especially TOEFL PBT (paper-based), although most countries across the world now prefer to use TOEFL iBT. This study examines the high frequency words in TOEFL ITP exercises and their morphological processes using a corpus data taken from the reading practices of Longman TOEFL PBT Preparation book. This study is a mix between a quantitative and a qualitative research. In finding the HFWs, the author used a software called AntConc. The results of the study showed that from 100 HFWs found in the reading section of TOEFL PBT exercises, the ranks of the most frequent word class to appear from highest to lowest are Noun (30 words), Verb (17 words), Adverb (15 words), Preposition (13 word), Determiner (11 words), Adjective (5 words), Number (4 words), Conjunction (4 words) and 1 Contraction. Meanwhile, the 10 most frequent words to appear among those 100 words are “the” (9,64%), “of” (4,24%), “in” (3,24%), “to” (2,56%), “a” (2,18%), “is” (1,77%), “and” (1,75%), “that (1,34%), “passage” (1,1%), and “on” (0,9%).